Social Identity and Perceived Income Adequacy - Deepti Goel; Ashwini Deshpande (Global Labor Organization (GLO), 2018)
Economists are increasingly interested in subjective well-being, but the economic literature on perceptions of income adequacy, which is one of the factors that shapes subjective well-being, is small. Our paper fills this lacuna in the literature. We utilize nationally representative data on perceptions of amounts considered as remunerative earnings from self-employment in India, and examine how these are shaped by social identity, namely, caste. We also investigate if institutional change such as the introduction of an employment guarantee scheme alters these perceptions. Finally, we examine the relationship between caste identity and actual earnings. We find that caste identity does shape both perceptions of income adequacy as well as actual earnings: lower-ranked groups perceive lower amounts as being remunerative, and also earn lower amounts. Further, the employment guarantee scheme alters self-perceptions differentially for different caste groups, but in more nuanced ways than our ex-ante beliefs.
Keywords: J15; O15; 330; Caste; Perceptions; Income Adequacy; Discrimination; India